Hubungan Antara Body Shaming Dan Citra Diri Dengan Kecemasan Sosial Pada Siswa SMP Ekasakti Semarang - Intan Ayu Setyorini (Program Studi Bimbingan dan Konseling, FKIP Universitas Pancasakti Tegal, 2021)
Verbal speech can make people affected by body shaming become down, lazy to do anything, cry, and become sad. The role of teachers and parents is very important in terms of providing support to students who are victims of body shaming and need to take firm action from the school concerned. The population in this study were students of class VIII SD class IX SMP Ekasakti Semarang, totaling 210 female students. The data collection method used a questionnaire with a Likert scale instrument consisting of four options. The test results show that there is a positive and significant relationship between body shaming and social anxiety, so the higher the body shaming, the higher the social anxiety, conversely the lower the body shaming, the lower the social anxiety, the two variables are strongly correlated, meaning that the higher the image. The students themselves will have lower social anxiety, on the other hand, the lower their self-image, the higher their social anxiety, so the two variables have strong correlation.